Hybrid Bio-Inorganic Materials for Environmental Remediation - Khan, Sher Wali; Bibi, Rifhat (New Environmentally-Friendly Materials, 2023)
Environmental pollution from heavy metals, persistent organic compounds, and emerging contaminants poses a growing threat to ecosystems and human health. Remediation processes have typically been associated with high costs, low selectivity, and secondary wastes, prompting a search for greener solutions. Mixed into renewable biopolymers with reactive metal oxides, hybrid bio-inorganic materials have become a promising general choice in pollutant capture and degradation. The basic characteristics of biopolymers and metal oxides, approaches to their synthesis and combination, and the synergistic effects that enhance the performance of the combination by exploiting synergies not present with the separate components are reviewed. The removal of heavy metals, dyes, pesticides, pharmaceuticals, and PFAS is shown as a case study, demonstrating the material’s versatility with different classes of pollutants. Important issues regarding stability, scaling up, and ecological security are critically discussed, and newer areas of research, including green synthesis, interface engineering, and the design of multifunctional materials, are growing. Hybrid bio-inorganic materials have the potential to contribute towards high-efficiency, low-impact remediation strategies. These materials can be adapted to a variety of environmental situations as they incorporate chemical diversity, structural stability, and catalytic activity into the same platform.